Instagram sebagai Media Periklanan Pentingnya Hidup Bersih dan Sehat di Wilayah Pesisir Desa Tlontoraja Kecamatan Pasean - Kurli, Anis; Wardita, Yulia; Elserisa, Lily; Nurul Hakim, Moh.; Andrianto, Ahmad (PUBLIC CORNER, 2023)
The importance of clean and healthy living behavior in the coastal area of Tlontoraja Village must continue to be increased, despite the increasing number of various health problems that occur. Socialization and education can use various types of social media, one of which is Instagram social media, which is now starting to be loved by all levels of society regardless of age. The research method used is qualitative research. Qualitative research is research that uses methods, steps and procedures involving several data and information obtained through several informants as subjects to obtain information and answers to phenomena that are occurring and being researched. The results of this research relate to the role of social media Instagram as an advertising medium for the importance of clean and healthy living in the Tlontoraja Coastal area, Pasean District, there are changes in people's behavioral patterns and thought patterns regarding the importance of clean and healthy living in the environment. A good environment is an environment that makes its residents calm, healthy and prosperous. To achieve this, it requires the involvement of all interested parties, one of which is the local community. Clean and healthy living behavior has made the people of the Tlontoraja Coastal District of Pasean independently play an active role in preventing disease outbreaks and improving health and keeping the environment clean from various pollution that occurs. This can minimize the emergence of various diseases that will cause health problems.